Lower Segment Cesarean Section for Guillain- Barre Syndrome - A Novel Anaesthetic Technique - Bhattarai, Rupak; Lamichhane, Sabina; Das, Chitta Ranjan (Birat Journal of Health Sciences, 2021)
Introduction: Guillain Barre Syndrome in pregnant ladies, undergoing cesarean section, has not yet reported in Nepal. Anaesthetic management of 15 patients with Guillain Barre Syndrome who underwent lower segment cesarean section at Nobel Medical College Teaching Hospital is reported here.Objective: The purpose of this study is to assess the benefits of Rectus sheath nerve block along with infiltration of retropubic space of Retzius in Guillain Barre syndrome patients planned for lower segment cesarean section (LSCS).Methodology: During the period from 1st August 2015 to 31st April 2020 at NMCTH, a retrospective descriptive analysis of 15 pregnant ladies with Guillain Barre Syndrome who underwent lower segment cesarean section under Rectus sheath nerve block along with Retro pubic space of Retzius, infiltration and visceral peritoneum infiltration is discussed.Result: Considering Surgeons opinion about the operating conditions like Relaxation, Straining, Coughing, Bucking, Satisfactory to good operative conditions were reported. Excellent to good satisfaction was expressed by 39.9% of patients, 60% patients reported satisfactory. Hypotension and Arrhythmias was seen in 2 patients. Diaphoresis was seen in 1 patient. Fetomaternal outcome was good. There was no mortality.Conclusion: Rectus sheath block along with infiltration of retro pubic space of Retzius block can be considered as a good alternative to general anaesthesia or neuraxial block incase where general anesthesia & neuraxial block is risky or contraindicated for lower segment cesarean section in patients with Guillain Barre Syndrome.